2010
DOI: 10.1021/cg100202h
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Induced Segmentation of Magnesian Calcite Thin Films Growing on a Calcite Substrate

Abstract: In crystal growth of mineral species or different compositional members of a solid solution on one another, the degree of lattice mismatch at their interface affects the growth pattern of the precipitating mineral phase. Fast layer-by-layer growth of magnesian calcite on pure calcite (1014) substrates has been observed at Mg 2þ /Ca 2þ ratios of 2-7 using in situ atomic force microscopy. Under solution conditions of calcite saturation states starting from Ω ≈ 33, depending on Mg 2þ /Ca 2þ ratios and carbonate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 43 publications
7
25
0
Order By: Relevance
“…Our results show that the growth is mainly controlled by the misfits between the overgrowth and substrate surface lattices. The relatively high lattice misfits (higher than 2.2%) determine a Volmer-Weber epitaxial growth mode, in agreement with previous AFM investigations on epitaxial growth on the surfaces of trigonal carbonates 5,10,14 and sulphates with the barite structure [25][26][27][28] .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our results show that the growth is mainly controlled by the misfits between the overgrowth and substrate surface lattices. The relatively high lattice misfits (higher than 2.2%) determine a Volmer-Weber epitaxial growth mode, in agreement with previous AFM investigations on epitaxial growth on the surfaces of trigonal carbonates 5,10,14 and sulphates with the barite structure [25][26][27][28] .…”
Section: Discussionsupporting
confidence: 88%
“…In addition, an estimate of the surface energy from dissolution at different saturation states showed that the monolayers on dolomite have an excess of interfacial strain energy 9 . Similar experiments to those conducted by Higgins and Hu 9 but using calcite (104) faces as substrates, resulted in a more complex growth behaviour [11][12][13][14] . At moderate supersaturated solutions with respect to both dolomite and Mg-calcites, and low magnesium contents, continuous layer-by-layer growth mechanism was reported.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…1996]. This hypothesis was later supported by in situ atomic force microscopy (AFM) data [Davis, K. J., Dove, P. M. et al 2000;Davis, K. J., Dove, P. M. et al 2004;Wasylenki, L. E., Dove, P. M. et al 2005;Stephenson, A. E., DeYoreo, J. J. et al 2008;Astilleros, J. M., Fernandez-Diaz, L. et al 2010;Sethmann, I., Wang, J. W. et al 2010;King, H. E., Satoh, H. et al 2013] which showed that Mg incorporation at calcite growth steps is indeed crystallographic direction specific. It was further suggested that the preferential incorporation of Mg in acute steps hinders the growth kinetic and weakens the surface energetic control on step orientations, and ultimately leads to the rounding of growth steps [Falini, G., Gazzano, M. et al 1994;Zhang, Y. P. and Dawe, R. A.…”
Section: Introductionmentioning
confidence: 94%
“…There are numerous examples of crystal surfaces undergoing changes of nanotopographic features during growth from aqueous solutions containing foreign ions [1][2][3][4][5][6][7]. One of the most remarkable phenomena is the so-called "template effect", which was first defined by Astilleros [8] to describe the reproduction of the original nanotopography of a crystal surface, including etch-pits and step edges, after successive completion of advancing monolayers.…”
Section: Introductionmentioning
confidence: 99%